Enhancing the combustion and safety performance of Al@AP Core-Shell structures with boron nitride - Jiahui Shi; Jiahao Liang; Yingjun Li; Xiaolu Bi; Haijun Zhang; Xueyong Guo; Shi Yan; Junwei Li; Jianxin Nie (Fuel Processing Technology)
Enhancing energy release and safety performance of energetic materials has garnered significant attention in composite solid propellants. Boron nitride (BN), known for its high thermal conductivity and lubricating properties, is a promising additive. To explore its application in propellants, Al@AP core-shell structure particles were prepared using an in situ deposition method. Structural characterisation, thermal decomposition properties, combustion characteristics, and safety of BN-doped Al@AP samples were evaluated using SEM, BET, XRD, DSC-TG-FTIR, closed bomb, laser ignition, and BAM standards. The results confirmed that AP effectively coated Al to form a typical core-shell structure, and BN was successfully incorporated into the Al@AP framework. BN promoted the thermal decomposition of Al@AP; at 0.5 wt% and 1.0 wt% BN, the low-temperature decomposition temperature of AP decreased by 28.01 °C and 26.85 °C, while the high-temperature decomposition temperature dropped by 6.41 °C and 5.25 °C, respectively. Closed bomb and laser ignition experiments indicated that with increasing BN content, the pressure rise rate and combustion intensity initially increased and then decreased. At 0.5 wt% and 1.0 wt% BN, the maximum pressure reached 127.93 kPa and 155.97 kPa, with corresponding pressure rise rates of 19.12 kPa/ms and 11.80 kPa/ms. The addition of BN significantly improves the safety performance of Al@AP, considerably reducing its impact and friction sensitivities. These findings demonstrated that when the BN content was 0.5 wt% and 1.0 wt%, both the combustion characteristics and safety of Al@AP were improved, achieving a practical balance and providing design guidance for the application of BN-doped Al@AP in solid propellants.